Young EFL learners and collaborative writing: A study on patterns of interaction, engagement in LREs, and task motivation. (November 2020) - Azkarai, Agurtzane; Kopinska, Marta
Abstract: Research on collaborative writing has analysed the patterns of interaction and language-related episodes (LREs) that occur during interaction. This research has mainly focused on adults, with a growing interest in young learners (YLs). However, research on patterns of interaction and LREs with YLs, and more specifically the level of engagement in which LREs are dealt with, is still scarce. This study brings these two issues together, and explores the patterns of interaction and level of engagement in LREs of a group of young Spanish EFL learners (ages 11–12) who worked in pairs on a dictogloss task. It does so by also focusing on these YLs' task motivation, that is, their attitudes towards the dictogloss they performed. The participants worked in pairs on this task and were asked to complete a motivation thermometer before and after completing the task. Then their oral interactions while performing the task were analysed examining the level of engagement in LREs, and patterns of interaction, and the relationship between these three variables: motivation, level of engagement in LREs and patters of interaction. The results showed mixed findings for patterns of interaction, with a similar amount of pairs represented by a collaborative pattern and a cooperative pattern; however, the engagement in LREs was not affected by the patterns of interaction, as the great majority of LREs were handled with high engagement. Regarding task motivation, these YLs showed an overall positive disposition towards the dictogloss task.